Sexual politics and rape in the selected works of Shashi Deshpande: a feminist Perspective - Sen, Nandita (Brac University, 2020)
This thesis report is submitted in partial fulfilment of the requirements for the degree of Masters of Arts in Teaching to Speakers of Other Languages, 2019.